From Bowling Guides to Superstar Biographies – Translated Sports Literature in Finland 1972-2019 - Nordman, Rasmus (My University, 2020)
This thesis presents a description of translated sports literature with English or Swedish as original language published in Finland between 1972 and 2019. The research material was acquired from The Finnish National Library and contains a total of 735 sports-related books. The thesis collects and analyses data concerning publishers and translators of sports-related literature, the represented sports disciplines, the functions of the studied literature and a comparison of translations from the two source languages. The thesis includes an examination of adaptations to better fit Finnish conditions made to some translations. In addition, several further research opportunities are presented. The publications in the research material are categorised according to original language, year of publication, author, publisher, translator, sports discipline and function. This categorisation provides an abundance of statistical data, which illuminates the overall situation and trends in the field of translated sports literature in Finland. In addition, a sample of six publications which have been adapted to better fit Finnish conditions are examined in order to illustrate the type of adaptations found in the research material. The categorisation of the research material shows a significant increase in translated sports literature during the studied time period. Although several publishing houses are represented in the research material, few publishing houses are responsible for the majority of all publications. The most represented sports disciplines are equestrian sports, football, strength training, golf, ice hockey sailing and hiking. Guides are the most common function of the publications followed by reviews and biographies. The share of English as original language has increased throughout the studied time period. Opportunities for further research include collecting a more extensive research material, comparing translated sports literature to sports literature originally written in Finnish and conducting similar research in another country or region. In addition, translators and publishers of translated sports literature could be studied more closely.
Keywords: translation, sports, sports literature